KONFLIK TOKOH UTAMA DALAM NOVEL RE: KARYA MAMAN SUHERMAN: KAJIAN PSIKOLOGI SASTRA - Utomo, Arie Lila; Qomariyah, U’um; Sumartini, Sumartini (Jurusan Bahasa dan Sastra Indonesia Universitas Negeri Semarang, 2019)
Tujuan penelitian ini adalah mendeskripsikan fenomea konflik yang dialami tokoh utama dalam novel Re:karya Maman Suherman. Mengetahui bentuk konflik dan upaya penyelesaian konflik yang dialami tokoh utama dalam novel Re:karya Maman Suherman.Pendekatan yang digunakan dalam penelitian ini adalah psikologi sastra Karen Horney yang menitikberatkan sastra sebagai cerminan masyarakat. Hasil dari penelitian ini adalahmengetahui fenomena konflik yang terdapat dalam novel yang kemudian dikorelasikan dengan kehidupan nyata. Korelasi konflik dalam novel dengan kehidupan nyata dapat dilihat dari adanya persamaan konflik yang terdapat dalam novel Re: karya Maman Suherman dengan kehidupan nyata.   The purpose of this research is describe life phenomenon of conflict which is experiencedthe main character in the novel titled Re: by Maman Suherman. Understandingform of conflict and conflict resolution efforts experienced by the main characterthe novel Re: by Maman Suherman. Approach used in this research is psychology literature of Karen Horney which is focusing literature as society reflection. The result of this research is was to knowthe phenomenon of conflict disclosures contained in the novel and then corelating with the real life of society. The corelation between conflict in the novel with real life can be seen from the equation of the conflict contained in the novel Re: by Maman Suherman and in the real life is able to be found from similarity of conflictwhich is existed in the novel and existed in the real life.The approach in this study is the psychology of literature Karen Horney, Results froms this study is the disclosure of conflict present in the novel then correlated with in real life. Correlation of conflict in the novel with of real life can be seen from equation of conflict in the novel Re: by Maman Suherman with real life.